Geology of the Areão Natural Park in João Monlevade (MG) from the perspective of the geoconservation of the quadrilátero ferrífero (iron quadrilateral) (Research, Society and Development, 2020)
The name of the “Areão” natural park refers to the intensive extraction of sand, which started in the mid-60s and ended in the 90s of the 20th century. However, only in 2012, the Areão Municipal Natural Park was created with an area of 24 hectares, in João Monlevade, Minas Gerais. The purpose of the research was to know the geological nature of the park in a detailed scale. The generated information can then be used for decision-making that aimed at geoconservation in the park region (environmental education, geoscientific diffusion , geoturism, etc.). It was sought to understand the reality of the phenomena, based on qualitative data, that is, descriptive. The work was done in four stage: Bibliographic research; site evaluation; petrographic analysis (mineralogical composition, texture, etc.) In the laboratory and at last, the interpretative phase that alowed to infer what was the stratigraphic framework of the park in the geology of the quadrilátero ferrífero (iron quadrilateral). The lithology that predominates in the outcrops of the central rocky walls of the park is a sericitic quartzite, which tends to become more rusting close to the highest levels. Underlying the quartzites a relatively altered muscovite-schist layer appears These metasedimentary rocks are correlated to the Minas Supergroup, characteristic of quadrilátero ferrífero (iron quadrilateral). Therefore, the park does correspond to an important geoconservation unit representative of the quadrilátero ferrífero (iron quadrilateral). In its geological diversity it is possible to interpret structures and facies deposition, deformation events and other features of the quadrilátero ferrífero (iron quadrilateral). In this context, the recognition of geology can become an important approach towards sustainability.